Use of Neuropathic Pain Questionnaires in Predicting the Development of Failed Back Surgery Syndrome following Lumbar Discectomy for Radiculopathy. Issue 1 (April 2016) - Shamji, Mohammed; Shcharinsky, Alina
Objective: Failed back surgery syndrome has been historically used to describe extremity neuropathic pain in lumbar disease despite structurally corrective spinal surgery. It is unclear whether specific preoperative pain characteristics predict patients prone to such postoperative disabling symptoms. Clinical predictors of patients unlikely to improve following surgical intervention has significant implications on patient selection to undergo spinal surgery. Methods: This prospective study analyzed consecutive surgical microdiscectomy patients treated for lumbar degenerative painful radiculopathy. Clinical parameters included general demographics, preoperative and postoperative clinical examination, self-reported pain and disability scores, and neuropathic pain scoring. The neuropathic pain screening tests used in this study were the Douleur Neuropathique 4 (DN4) and Leeds Assessment of Neuropathic Symptoms and Signs (LANSS), with correlation tested using Spearman's correlation coefficient for ordinal score and screen positivity. Multiple logistic regression analysis was used to define predictors of postoperative symptomatology. Results: Twelve percent of the 250 surgical radiculopathy patients underoing microdiscectomy experienced persistent postoperative neuropathic pain (PPNP) with only modest if any relief of leg pain. The condition was highly associated with abnormal preoperative screens for neuropathic pain, but not gender, smoking status, or preoperative pain severity (α=0.05). Good correlation was seen between the two screening tests used in this study for both absolute ordinal score (Spearman's ρ=0.84, p < 0.001) and thresholding for terming the patient as having neuropathic pain features (Spearman's ρ=0.48, p < 0.001). Younger age at treatment also correlated with a higher likelihood of developing PPNP ( p = 0.03). With regards to predictive value, the positive and negative predictive values for FBSS are 40% and 97% for the DN4 and 70% and 96% for the LANSS respectively. Conclusion: This cohort of surgical patients was evaluated using validated neuropathic pain screening tools to understand the presence of these features among lumbar radiculopathy patients. Good correlation was seen between both DN4 and LANSS screening tools, suggesting that neuropathic pain diagnosis does exist among a surgical cohort of lumbar radiculopathy patients, with further findings that exceeding established threshold values portends worse prognosis for postoperative recovery. These findings will better inform both patient and surgeon with regards to surgical expectations and decision-making for cases where neuropathic pain features exist, and screening for such diagnosis is recommended in a complete evaluation of the spine surgical patient. References Asch HL, Lewis PJ, Moreland DB, et al. Prospective multiple outcomes study of outpatient lumbar microdiscectomy: should 75 to 80% success rates be the norm? J Neurosurg 2002;96(1, Suppl)34–44 Unal-Cevik I, Sarioglu-Ay S, Evcik D. A comparison of the DN4 and LANSS questionnaires in the assessment of neuropathic pain: validity and reliability of the Turkish version of DN4. J Pain 2010;11(11):1129–1135 Voorhies RM, Jiang X, Thomas N. Predicting outcome in the surgical treatment of lumbar radiculopathy using the Pain Drawing Score, McGill Short Form Pain Questionnaire, and risk factors including psychosocial issues and axial joint pain. Spine J 2007;7(5):516–524